1989
DOI: 10.1086/629332
|View full text |Cite
|
Sign up to set email alerts
|

Upper Mantle Oxygen Fugacity and Its Relationship to Metasomatism

Abstract: We have calculatedf0 2 's and temperatures of various mantle environments worldwide using published analyses of coexisting olivine, orthopyroxene, clinopyroxene, and Fe 3 +-bearing spinel from 280 peridotites. Most calculated /0 2 's fall within ± 2 log units of the Fayalite-Magnetite-Quartz (FMQ) buffer at 15 kbar. Our data set defines a general trend in/Or T space that is not related to FMQ or to other Fe-bearing buffers. Variations in major-element, trace-element, and oxygen isotopic composition of xenolith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…Olivine deformation is influenced by the chemical environment in which it occurs. Subduction carries down volatiles that promote magma genesis (Anderson, Uyeda & Miyashiro 1976;Tatsumi 1986), metasomatize the sub-arc mantle (Maury, Defant & Joron 1992), and locally oxidize it (Mattioli et al 1989;Wood, Bryndzia & Johnson 1990). Oxidizing conditions make olivine more deformable (Kohlstedt & Hornack 1981;Ryerson et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Olivine deformation is influenced by the chemical environment in which it occurs. Subduction carries down volatiles that promote magma genesis (Anderson, Uyeda & Miyashiro 1976;Tatsumi 1986), metasomatize the sub-arc mantle (Maury, Defant & Joron 1992), and locally oxidize it (Mattioli et al 1989;Wood, Bryndzia & Johnson 1990). Oxidizing conditions make olivine more deformable (Kohlstedt & Hornack 1981;Ryerson et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of Fe 2+ and Fe 3+ in spinel was inferred from stoichiometry. The mantle fugacity values obtained by this method (Ballhaus, 1993;Mattioli et al, 1989) differ little from those obtained by direct determinations of Fe 3+ .…”
Section: Oxygen Fugacitymentioning
confidence: 63%
“…In comparison, the studied megacrysts and kaersutite sample Fr-12 from the Massif Central, France (Dyar et al 1993) are among the most ferricrich compositions recorded. Mattioli et al (1989) suggested that patent metasomatism, which introduces ferric-rich amphibole, might lead to greater enrichment of bulk Fe 3+ and an apparent greater metasomatic redox effect. Redox conditions (f O 2 and Fe 3+ /FeO tot ) determine the stability of C-O-H-S fl uid and solid phases in the mantle.…”
Section: Oxygen Fugacitymentioning
confidence: 99%